In Amazonia : A Natural History - Raffles, Hugh, 1958- (Book collections on Project MUSE., 2002)
The Amazon is not what it seems. As Hugh Raffles shows us in this captivating and innovative book, the world''s last great wilderness has been transformed again and again by human activity. In Amazonia brings to life an Amazon whose allure and reality lie as much, or more, in what people have made of it as in what nature has wrought. It casts new light on centuries of encounter while describing the dramatic remaking of a sweeping landscape by residents of one small community in the Brazilian Amazon. Combining richly textured ethnographic research and lively historical analysis, Raffles weaves.